Combined optimization of continuous wind turbine placement and variable hub height. Issue 180 (September 2018) - Wang, Longyan; Cholette, Michael E.; Fu, Yanxia; Yuan, Jianping; Zhou, Yunkai; Tan, Andy C.C.
Abstract: This paper aims to systematically study the wind farm optimization with the continuous selection of wind turbine placement (using Cartesian coordinates) and wind turbine hub height (restrained among a predefined range). Two case studies are performed. The first case involves an ideal two-dimensional (i.e., flat terrain) wind farm, and the other is a three-dimensional wind farm with real terrain altitudes. The schemes of simultaneously optimizing the wind farm layout and wind turbine hub heights applying the simplified and augmented PARK wake model are established for the ideal and real wind farm cases, respectively. The results show that applying different wind turbine hub heights for the wind farm layout optimization yields significant improvement: up to a 0.2 MW increase in total power and a 2% increase of the wind farm efficiency for the ideal wind farm. However, for the real wind farm the effectiveness of applying different wind turbine hub heights varies depending on the number of turbines installed. With less number of turbines installed, the impact of varying hub heights is small. However, significant improvements can be achieved as the number of turbines increases. With 39 wind turbines, the wind farm cost of energy can be reduced by 15000 per megawatt and the wind farm efficiency can increase by up to 0.2%. Given the nameplate capacity and the lifespan of wind farm project, the resulting effect on total energy production can be significant and thus improve the competitiveness of wind power exploitation. Highlights: A combined optimization of wind turbine positions and hub heights is conducted with continuous variation. A computationally-efficient method considering wake effect over non-flat terrain is applied. Ideal wind farm yields 0.2 MW more power and 2% increase in efficiency with maximum hub height difference of 40 m. Real wind farm reduces cost of energy by 15000 per megawatt with maximum hub height difference of 40 m.